Packed Bed Biosorption of Lead and Copper Ions Using Sugarcane Bagasse - Duga, Norwin Dale F.; Imperial, Pauline Edrickke A.; Soriano, Allan N; Nieva, Aileen D (ASEAN Journal of Chemical Engineering, 2016)
Bagasse, a waste material from sugarcane has been studied as a biosorbent for removing heavy metals, Pb2+ and Cu2+, in a continuous system using a packed bed column. This study was undertaken to determine the influence of varying the bed height and flow rate on the breakthrough and saturation time. Thomas, Adams-Bohart and Yoon-Nelson models were used to assess the effects of varying parameters and both Thomas and Yoon-Nelson models were found to be satisfactory to describe the column data obtained in the experiment. Moreover, lead ions are adsorbed more efficiently with an adsorption capacity of 4.54 mg/g compared to copper ions with 3.98 mg/g at the most feasible parameters having a flow rate of 100 mL/min and a bed height of 30 cm